Polycystic ovary syndrome: a dermatologic approach - Moreira-Gomes,Patrícia (2024)
Abstract Polycystic ovary syndrome (PCOS) is one of the most common endocrinopathies in women of reproductive age. It is a multifactorial disease with endocrinological, genetic, and environmental factors playing a role in its pathophysiology. The main diagnostic criteria include the presence of hyperandrogenism, chronic anovulation, and polycystic ovaries on ultrasound. Women with PCOS present a variety of signs and symptoms, as well as an increased risk of metabolic, cardiovascular, and reproductive disorders. This syndrome has an important psychological impact, and it is associated with a decreased quality of life. The dermatological manifestations, due to hyperandrogenism, include hirsutism, acne, and androgenetic alopecia. These manifestations provide clues for PCOS diagnosis, and early treatment is essential to improve the quality of life and well-being of patients. Thus, as part of a multidisciplinary approach, dermatologists play an essential role in the diagnosis and treatment of women with PCOS. Treatment includes hormonal therapy to control hyperandrogenism and non-hormonal therapy for each dermatological manifestation.